Effect of salivary stimulant on liquid turnover rate and microbial protein synthesis in the rumen of buffaloes - MASSON, PRADEEP; NANGIA, O P (The Indian Journal of Animal Sciences, 2013)
Ginger supplementation as salivary stimulant in the diet of buffaloes resulted in significant increase in rumen fluid outflow Tutc and microbial protein synthesis. The results indicated that it may be possible 10 after heneficially the efficiency of rumen microbial protein synthesis via saliva-induced changes in ruminal liquid flow by using an exogenously administered sialagogue.